Airway Adventures of Airtraq: Use of Airtraq Optical Laryngoscope with Adaptor in Infants with Obstructive Hydrocephalus Posted for Endoscopic Third Ventriculostomy - Shahna Ali; Hassan Rashid; Obaid A. Siddiqui; Manazir Athar (Journal of Neuroanaesthesiology and Critical Care, 2020)
The pediatric airway is a challenge for the anesthetist due to difficulty in adequate assessment, scarcity of management algorithms, lack of precise knowledge regarding incidence, as well as limitations of the various devices, instruments, and video laryngoscopes. We present a case series of infants with obstructive hydrocephalus with anticipated difficult intubation posted for endoscopic third ventriculostomy (ETV) in whom the airway wtas successfully secured using Airtraq optical laryngoscope with adaptor. Although this device has not been widely studied in pediatrics age group, there are different sizes available for use among children. The ease of use, short learning curve, low cost, single use, and successful approach to difficult airway have made it to being the main rescue technique when the initial approach has failed.